Amniotic fluid cathepsin-G in pregnancies complicated by the preterm prelabor rupture of membranes - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Soucek, Ondrej; Pliskova, Lenka; Stepan, Martin; Bestvina, Tomas; Maly, Jan; Jacobsson, Bo; Kacerovsky, Marian (The journal of maternal-fetal & neonatal medicine, 2017)
OBJECTIVE: The aim of this study was to evaluate the amniotic fluid cathepsin-G concentrations in women with preterm prelabor rupture of membranes (PPROM) based on the presence of the microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation (IAI). METHODS: A total of 154 women with singleton pregnancies complicated by PPROM were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis. Amniotic fluid cathepsin-G concentrations were assessed by ELISA. MIAC was determined using a non-cultivation approach. IAI was defined as an amniotic fluid bedside interleukin-6 concentration ≥ 745 pg/mL. RESULTS: Women with MIAC had higher amniotic fluid cathepsin-G concentrations than women without MIAC (with MIAC: median 82.7 ng/mL, versus without MIAC: median 64.7 ng/mL; p = 0.0003). Women with IAI had higher amniotic fluid cathepsin-G concentrations than women without this complication (with IAI: median 103.0 ng/mL, versus without IAI: median 66.2 ng/mL; p < 0.0001). Women with microbial-associated (with both MIAC and IAI) IAI and sterile (IAI without MIAC) IAI had higher amniotic fluid cathepsin-G concentrations than women with colonization (MIAC without IAI) and women without both MIAC and IAI (p < 0.0001). CONCLUSIONS: The presence of either microbial-associated or sterile IAI was associated with increased amniotic fluid cathepsin-G concentrations in pregnancies complicated by PPROM. Amniotic fluid cathepsin-G appears to be a potential marker of IAI.
Keywords: serine protease; dospělí; Enzyme-Linked Immunosorbent Assay; Female; předčasný odtok plodové vody; biologické markery; Amniocentesis; Biomarkers; Adult; mladý dospělý; ženské pohlaví; lidé; PPROM; těhotenství; předčasná porodní činnost; studie případů a kontrol; Interleukin-6; preterm delivery; Fetal Membranes, Premature Rupture; retrospektivní studie; ELISA; amniocentéza; Cathepsin G; Case-Control Studies; Cathepsin-G; Amniotic Fluid; plodová voda; Young Adult; interleukin-6; inflammation; Obstetric Labor, Premature; neutrophil; Pregnancy; Retrospective Studies; kathepsin G; Humans